ДІАЛЕКТИКА ВЗАЄМОВІДНОСИН «Я»–«ІНШИЙ»–«ЧУЖИЙ» У ПОЛІКУЛЬТУРНОМУ ДИСКУРСІ СУЧАСНОСТІ - Культенко, В. П. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 1970)
Досліджуються проблеми співіснування людей в сучасному глобальному світі в контекстіактуальних дискурсів сучасності – полікультурності та мультикультуралізму, метою яких єподолати культурні суперечності у світі, допомогти людині включити іншого та чужого у свійжиттєвий світ, навчитись сприймати, чути, розуміти та співпереживати іншому-чужому,через нього відкриваючи й себе, поглиблюючи розуміння себе. Це є умовою нормального розвиткусвіту, в якому силові засоби, державні кордони та національні бар’єри не убезпечують відкультурного протистояння, що часто доходить до своїх крайніх меж.Ключові слова: інший, чужий, полікультурність, мультикультуралізм, глобалізація,комунікація, солідаризм, толерантність.В.П.Культенко. Диалектика взаимоотношений «Я»-«Другой»-«Чужой» в современномполикультурном дискурсе. Исследуются проблемы сосуществования людей в современномглобальном мире в контексте актуальных дискурсов современности – поликультурности имультикультурализма, целью которых является преодолеть культурные противоречия в мире,помочь человеку включить другого и чужого в свой жизненный мир, научиться воспринимать,слышать, понимать и сопереживать другому-чужому, через него открывая и себя, углубляяпонимание себя. Это является условием нормального развития мира, в котором силовыерепрессивные средства, государственные границы и национальные барьеры не ограждают откультурного противостояния, часто доходящего до своих крайних пределов.Ключевые слова: другой, чужой, поликультурность, мультикультурализм, глобализация,коммуникация, солидаризм, толерантность.V. Kultenko. Dialectic of relations «I»-«Other»-«Alien» in Modern polyculturals discourse. In thisarticle the author investigates the problems of humans’ coexistence in the modern global world in thecontext of such actual discourses of modernity as polyculture and multiculture which aim is to defeat thecultural rivalries in the world, to help human with integration of other, alien things in its own life, to helpwith learning to realize, hear, understand other people. This is a condition of normal world developmentwhere military actions, state borders do not provide the isolations from cultural conflict, which oftenreaches to its extreme borders. With help of integration of others in your own life, the formation of suchgenerally agreed rules of coexistence as moral and legal occurs. These moral and legal rules help tointegrate each others freedom into the general unity, without violation of others’ liberty. Acceptance ofother is possible with help of dialogue also with help of irrational ways of understanding such asreligious belief, emotional affection, art, muscularity etc. This article also deals with philosophicpositions of representatives of different streams, studies, philosophic traditions considering the solvationof the given problems, among other things article analyzes and compares positions of devotees ofliberalism, comunitarism, solidarism ideology, each of those proposes system of fundamental values,which must be put into the base of social understanding, achievement of necessary balance of powers andinterests in polycultural social environment.Key words: other, alien, polyculture, multicultural, globalization, communication, solidarism,tolerance.